Skating techniques of ladies' world-class long-distance speed skaters to shorten curved-section time during the official 3,000 m race - Kimura, Yuya; Yokozawa, Toshiharu (Frontiers in Sports and Active Living, 2024)
This study aimed to identify the factors contributing to expedited passage through curved sections in skating by analyzing centripetal acceleration and skating motions during curving in a 3,000 m race for ladies' world-class speed skating. It included 14 elite skaters participating in the ladies' 3,000 m race held during the World Cup. The recorded area consisted of the first inner curve lane. Skaters were recorded as they passed through the measurement range at the initial, middle, and final stages of the race. Three synchronized high-speed cameras were used to record skaters from the front, back, and side. From the images obtained by the high-speed camera, 21 body endpoints and 4 blade edges were digitized at 50 Hz using specialized digitizing software. Three-dimensional coordinates of the 25 points were obtained using a panning direct linear transformation technique. The stroke-averaged centripetal acceleration and kinematic parameters were calculated based on the three-dimensional coordinates of the body during the curve-skating motion. Centripetal acceleration had a significant effect on the curved-section time in all three race stages (initial: F = 17.19, middle: F = 23.30, final: F = 16.64) and significantly decreased as the race progressed (left: F = 9.42, right: F = 8.05). Throughout the race, the right and left shanks and the body's center of mass (CM) during the stroke were raised (shank angle: left: F = 13.62, right: F = 11.02, CM height: left: F = 21.15, right: F = 21.69). The body-tilt angle for both strokes and shank-tilt angle for the right stroke were significantly correlated with centripetal acceleration in all race stages (body-tilt: left: initial: r = 0.80, middle: r = 0.75, final: r = 0.89, right: initial: r = 0.78, middle: r = 0.84, final: r = 0.67, right shank-tilt initial: r = 0.80, middle: r = 0.77, final: r = 0.63). These results suggested that to reduce the skating time through curved sections, maintaining an inward body tilt and minimizing the decrease in centripetal acceleration even in the final race stage are crucial considerations. They also suggested that when leaning the body inward and maintaining centripetal acceleration, the right shank should be leaned inward for the right stroke and the left shank should be leaned inward for the left stroke, or the left blade should be positioned farther to the right of the CM.